In Vitro Test of Antioxidant Activity of Leilem Leaf Ethanol Extract (Clerodendrum minahassae) Using DPPH and FRAP Methods - Malino, Angeline Priscillia; Kepel, Billy Johnson; Budiarso, Fona Dwiana Hermina; Fatimawali, Fatimawali; Manampiring, Aaltje Ellen; Bodhi, Widdhi (Heca Journal of Applied Sciences, 2024)
The risk of degenerative diseases is increasing due to unhealthy lifestyles. Many people consume junk food, smoke, and do not protect themselves from sun exposure and pollution, exposing their bodies to free radicals. Free radicals can cause oxidative stress, necessitating the need for antioxidants to neutralize them. The leilem plant (Clerodendrum minahassae) is an endemic plant from North Sulawesi that is often used in traditional dishes and medicine. Moreover, leilem leaves are believed to be a source of natural antioxidants. This study aimed to determine the efficacy of leilem leaf ethanol extract as a source of antioxidants. The antioxidant potential was evaluated using phytochemical screening and antioxidant assays such as 2,2-Diphenyl-1-Picrylhydrazyl (DPPH) and Ferric Reducing Antioxidant Power (FRAP) methods, with ascorbic acid as a comparison. The level of antioxidant activity was measured by determining the IC50 value, which corresponds to the concentration of extract required to inhibit 50% of free radicals. The results of phytochemical screening showed that the ethanol extract of leilem (Clerodendrum minahassae) leaves contains active compounds such as phenols, flavonoids, saponins, tannins, steroids/triterpenoids, and alkaloids, indicating a high potential for antioxidant activity. The IC50 value for the DPPH method was 78.799 ppm, and the IC50 value for the FRAP method was 92.127 ppm. These results demonstrate that the ethanol extract of leilem leaves has strong antioxidant activity in both the DPPH and FRAP methods.